Open Science versus Data Protection – Challenges and Solutions in Sign Language Acquisition Studies - and Kolbe, Vera (Hrvatska revija za rehabilitacijska istraživanja, 2022)
Research within Deaf communities needs to adhere to the ethical requests of the partner communities involved. These ethical requests can be met via open science practices that are implemented in the project strategies of the European Commission. Open...
Keywords: Björn-2026-02-22